(untitled) (Alternautas, 2023)
This article examines the anti-monument La glorieta de las mujeres que luchan, designed and stealthily placed by the Mexican collectives Antimonumenta and the Frente Amplio de Mujeres que Luchan to recognise the socio-political relevance of the feminist activists, commemorate and name victims of feminicide, decolonise the city and question the patriarchal official historical narrative. The wooden statue of a girl and the renaming of the site took place on 25 September 2021, after Mexico City’s government removed the statue of Christopher Columbus (to protect it from activists) and proposed to replace it with a monument that reproduced colonialist and patriarchal political mechanisms. I argue that La glorieta de las mujeres que luchan is a useful tool to remember the feminist protest and a memorial for victims of feminicide; meanwhile, it confronts the patriarchal historic narrative. Since the statue resulted from consent amongst feminist groups, it successfully represents the majority of women engaging in different movements against gender-based violence. The statue is located in Paseo de la Reforma, the most important avenue in Mexico City, where only two of the monuments represent female figures (both mythological characters) surrounded by several representations of male heroes. Drawing on Suzanne Lacy’s concept of “new genre public art” (Lacy, 1995) –popularised in Mexico by feminist artist Mónica Mayer– and Julia Antivilo’s (Antivilo Peña, 2008) (‘Ponencia Arte Feminista-Julia Antivilo’, 2020) analysis of feminist activism, I argue that the anti-monument is a constant reminder of feminist’s demands and stands as a perpetual activist act.